Effect of Ensiling Density and Storage Temperature on Fermentation Quality, Bacterial Community, and Nitrate Concentration of Sorghum-Sudangrass Silage - Bai, Chunsheng; Pan, Gang; Leng, Ruoxuan; Ni, Wenhua; Yang, Jiyun; Sun, Juanjuan; Yu, Zhu; Liu, Zhigang; Xue, Yanlin (Frontiers in Microbiology, 2022)
This study aimed to evaluate the fermentation quality, bacteria community, and nitrate of sorghum-sudangrass silage with two silo densities (550 kg fresh weight (FW)/m3 (LD) and 650 kg FW/m3 (HD)) stored at two temperatures (10 C (LT) and 25 C (HT)) for 60 d. The fermentation parameters, microbial counts, bacterial community, nutrition composition, nitrate, and nitrite were assessed. Compared with LT-treatments, HT-treatments had lower pH and counts of lactic acid bacteria and yeasts and contained higher lactic acid (LA) and LA/acetic acid (LA/AA) (p < 0.05). The LT-LD contained more ammonia-N than LT-HD (p < 0.05) and had higher nitrate and percent of initially detected nitrate than other treatments (p < 0.05). Lactobacillus had the greatest abundance among bacterial genera in all treatments (57.2% - 66.9%). According to principal coordinates analysis, the bacterial communities of LT-treatments were separated clearly from HT-treatments. The nitrate concentration and the percent of initially detected nitrate in silage correlated negatively with LA, LA/AA, Pantoea, Pseudomonas, and Enterobacter (p < 0.05), and positively with pH and ammonia-N (p < 0.05). Overall, the silage with high density and temperature had greater satisfactory fermentation quality and nitrate degradation. The bacterial communities in all treatments were affected mainly by storage temperature and dominated absolutely by Lactobacillus. The nitrate degradation during fermentation process might be related to the fermentation quality and the activity of Pantoea, Pseudomonas, and Enterobacter in silage.